PENGARUH PUPUK POMI DAN NPK GROWER TERHADAP HASIL BAWANG MERAH (Allium ascalonicum L) - selvia sutriana (DINAMIKA PERTANIAN, 2016)
Shallot is the most important horticulture commodity as a cooking spice after chilli. The purpose of this research wa to know the effect of pomi fertilizer and NPK grower on shallot yield. The research was conducted at the expremental farm of Facuty of Agriculture Riau Islamic University Pekanbaru during three months, from December to February 2016. The randomized completely design with two factors was used. The first factor used pomi fertilizer (0, 5, 10, and 15 cc/l water), while the second factor was NPK grower (0, 10, 20, and 30 gr/plot). Parameters observed were number of tillers, tuber diameter, wet bulb weight per hill, wet bulb weight per plot, dry bulb weight per hill and weight of dried tuber per plot. The results showed that interaction had an effect on all observation parameters with best treatment of P2N3 (10 cc/l water of pomi fertilizer and NPK grower 30 g/plot). Mainly, fertilizer application gave an effect on all observation parameters with best treatment of P2 (10 cc / l water), whereas NPK grower application gave an effect on tuber diameter, wet bulb weight per hill, wet tuber weight per plot, tuber weight dry per hill and weight of dry bulb per plot with best treatment N3 (30 g/plot).